Preparation and Characterization of Low Expansion Transparent Copolyimide Films - ZHANG Ming-yan; CUI Hong-yu; WU Zi-jian; GAO Sheng; GAO Yan (Journal of Harbin University of Science and Technology)
To overcom the shortcoming of fluorinated polyimide films such as low reaction activity and high coefficien of thermal expansiont, rigid monomer pyromellitic dianhydride(PMDA) were used to copolymerize with two Fluorinated monomers 4,4(hexafluoroisopropylidene)diphthalic anhydride(6FDA) and 2,2bis(trifluoromethyl) benzidine(TFMB) to form a serials of PAA solution, as control, PI-4 were synthesized by PMDA and ODA (4,4 two amino two phenyl ether). After that, the obtained PAA solution was heated at the following order to produce transparent polyimide films, 80℃/1h, 110℃/2h, 150℃/2h, 200℃/1h, 250℃/30min, 300℃/30min, the obtained PI films which had pyromellitic dianhydride content of 0%, 20% and 40% were numbered as PI-1,PI-2,PI-3, relatively, and its phsical and chemical properties were characterized. The thermogravimetric analysis showed that thermal stability of fluorinated films is slightly lower than that of traditional film; the dielectric tests showed that the fluoride film’s dielectric constants were smaller than traditional polyimide film, the dielectric constant of PI-1 is less than PI-2 and PI-3 copolymer films; the UVVis spectra showed that the transmittance of fluorinated polyimide film was significantly higher than that of conventional film, cutoff wavelength and yellow index of PI-1, PI-2, PI-3 was 355 nm, 360 nm, 372 nm, and 6.4, 6.9 , 8.94, relatively.All three films’ transmittance at the wavelength of 500nm were more than 90%; the tensile test showed that the tensile strength of fluorinated polyimide films was much lower than that of the conventional polyimide, but it increased after the addition of rigid monomers; the thermal expansion coefficients of four kinds of films were 14.8×10-5 /℃, 9.9×10-5 /℃, 5.4×10-5 /℃and 4.0×10-5/℃,respectively, which were decreased with the increase of the content of of PMDA content.